PENERAPAN MODEL NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR IPS SMP KEMALA BHAYANGKARI 1 SUNGAI RAYA - Windiya Reni Triana; Sri Buwono; F.Y. Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was to found out to improving IPS learning outcome through Numbered Head Together (NHT) cooperative learning model at class VIII A SMP Kemala Bhayangkari 1 Sungai Raya. The design of this research was classroom action research with 2 cycles. Each cycle consisted of four stages, including planning implementation, action implementation, observation, and reflection. The research method was descriptive method. The subject of this research was 23 students at class VIII A. Data collection was conducted with direct observation technique, learning outcome measurement, and documentary of study. The tool of data collection used in this research was learning outcome test and observation sheet. The result finding showed that the level of success in learning that was determined by 75% but the implementation of Numbered Head Together (NHT) cooperative learning model at cycle I was not optimal because the level of success only reached 72%. Therefore at cycle II, it was optimal because the level of success was 100%. The mean score in post-test at cycle I and cycle II improved about 15.66%. The percentage of learning mastery in post-test at cycle I and cycle II improved about 21.74%. Keywords: Numbered Head Together, Learning Outcome, IPS